(untitled) (Revista Internacional de Folkcomunicação, 2022)
In the context of popular culture within the concept of folkcomunicacão created by Luiz Beltrão in 1967, it was observed that popular groups had difficulties in accessing the mass media, but that they had a peculiar form of communication through cultural manifestations. Currently, with the transformations of the mediatized society, new ambiences arise in the communicational relations between cultural groups with more democratized access. Thus, the media activists of the folk communication network, collectives, cultural groups and NGOs played an active and important role with the interpenetration of culture and communication in today’s society, resulting in citizenship actions in communication relations, creating new meanings and providing sustainability within the cultural groups.